Macular and submacular choroidal microvasculature in patients with primary open-angle glaucoma and high myopia. Issue 5 (10th December 2021) - Lin, Fengbin; Qiu, Zhen; Li, Fei; Chen, Yu; Peng, Yuying; Chen, Meiling; Song, Yunhe; Xiong, Jian; Cheng, Weijing; Liu, Yuhong; Tan, Mingkui; Zhang, Xiulan; et al.
Abstract : Aims: To characterise the influence of primary open-angle glaucoma (POAG) and high myopia (HM) on the macular and choroidal capillary density (CD). Methods: Two hundred and seven eyes were enrolled, including 80 POAG without HM, 50 POAG with HM, 31 HM without POAG and 46 normal controls. A fovea-centred 6×6 mm optical coherence tomography angiography scan was performed to obtain the CD of the superficial capillary plexus (SCP), deep capillary plexus (DCP) and choriocapillaris. Macular and choroidal CDs were compared among the groups and the association of CDs with visual field mean deviation (MD) was determined using linear regression models. Results: Compared with normal eyes, SCP CD was decreased in the POAG without HM group (p<0.05), while DCP CD was significantly decreased in the HM without POAG group (p<0.05). Both SCP and DCP CDs were significantly decreased in the POAG with HM group (p<0.05). CD reduction occurred mainly in the outer rather than inner ring of the 6×6 mm scan size. In multivariate regression analysis, worse MD was associated with lower CD in the outer ring of the SCP in all the HM eyes (p<0.05). Conclusions: POAG and HM reduced macular CD in different layers of the retinal capillary plexus and both particularly in the outer ring of the 6×6 mm scans. Furthermore, assessment of the CD in the outer ring of the SCP may facilitate the diagnosis of glaucoma in eyes with HM.